Effects of Tai Chi and brisk walking on the bone mineral density of perimenopausal women: A randomized controlled trial - Cheng, Liang; Chang, Shuwan; He, Benxiang; Yan, Yang (Frontiers in Public Health, 2022)
Background: There is a lack of information on whether the positive effect of Tai Chi (TC) and brisk walking (BW) exercise on BMD in perimenopausal women remains after exercise cessation. To compare the effects of regular TC and BW exercise on bone mineral density (BMD) in perimenopausal women and to analyze the maintenance effects after exercise cessation. Methods: The TC and BW groups performed 48 weeks of exercise. The BMD of the lumbar spine and dominant-side proximal femur was measured in all subjects at weeks 0, 48, 52, and 56. Results: Compared with baseline, the BMD of the lumbar spine (L2-4) at week 48 increased by 5.05% (P = 0.031) in the TC group, and the BMD of the femoral neck at week 48 increased by 8.23% (P = 0.031) in the BW group. At 4 and 8 weeks after exercise cessation, the BMD of L2-4 in the TC group was still increased by 5.05% (P = 0.041) and 5.05% (P = 0.023), respectively, and the BMD of the femoral neck was still increased by 8.23% (P = 0.018) and 9.41% (P = 0.007), respectively, in the BW group. Conclusion: Forty-eight weeks of TC exercise significantly increases the BMD of L2-4 in perimenopausal women, and BW exercise significantly increases the BMD of the femoral neck; these effects are maintained at 4 and 8 weeks after exercise cessation. These results suggest that these two exercises reduce the BMD decrease caused by aging.